Abnormalities in chromosome 6q24 as a cause of early‐onset, non‐obese, non‐autoimmune diabetes mellitus without history of neonatal diabetes. Issue 7 (11th April 2015) - Yorifuji, T.; Matsubara, K.; Sakakibara, A.; Hashimoto, Y.; Kawakita, R.; Hosokawa, Y.; Fujimaru, R.; Murakami, A.; Tamagawa, N.; Hatake, K.; Nagasaka, H.; Suzuki, J.; et al.
Abstract Aims Abnormalities in the imprinted locus on chromosome 6q24 are the most common causes of transient neonatal diabetes mellitus (6q24‐related transient neonatal diabetes). 6q24‐Related transient neonatal diabetes is characterized by the patient being small‐for‐gestational age, diabetes mellitus at birth, spontaneous remission within the first few months and frequent recurrence of diabetes after childhood. However, it is not clear whether individuals with 6q24 abnormalities invariably develop transient neonatal diabetes. This study explored the possibility that 6q24 abnormalities might cause early‐onset, non‐autoimmune diabetes without transient neonatal diabetes. Methods The 6q24 imprinted locus was screened for abnormalities in 113 Japanese patients with early‐onset, non‐obese, non‐autoimmune diabetes mellitus who tested negative for mutations in the common maturation‐onset diabetes of the young (MODY) genes and without a history of transient neonatal diabetes. Positive patients were further analysed by combined loss of heterozygosity / comparative genomic hybridization analysis and by microsatellite analysis. Detailed clinical data were collected through the medical records of the treating hospitals. Results Three patients with paternal uniparental isodisomy of chromosome 6q24 were identified. None presented with hyperglycaemia in the neonatal period. Characteristically, these patients were born small‐for‐gestational age, representing 27.2% of the 11 patients whose birth weight standard deviation score (SDS) for gestational age was below −2.0. Conclusions Abnormalities in the imprinted locus on chromosome 6q24 do not necessarily cause transient neonatal diabetes. Non‐penetrant 6q24‐related diabetes could be an underestimated cause of early‐onset, non‐autoimmune diabetes in patients who are not obese and born small‐for‐gestational age.